2015
DOI: 10.3390/jfb6010104
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Chitin, Chitosan, and Its Derivatives for Wound Healing: Old and New Materials

Abstract: Chitin (β-(1-4)-poly-N-acetyl-d-glucosamine) is widely distributed in nature and is the second most abundant polysaccharide after cellulose. It is often converted to its more deacetylated derivative, chitosan. Previously, many reports have indicated the accelerating effects of chitin, chitosan, and its derivatives on wound healing. More recently, chemically modified or nano-fibrous chitin and chitosan have been developed, and their effects on wound healing have been evaluated. In this review, the studies on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
116
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(135 citation statements)
references
References 177 publications
2
116
1
6
Order By: Relevance
“…Compared to chitin, chitosan is unique and found only in fungi that have deacetylase enzymes.
10.1080/21501203.2018.1473299-F0001Figure 1.Structural homology of linear polysaccharides. Chitin, chitosan and cellulose (Azuma et al 2015).
…”
Section: Introductionmentioning
confidence: 99%
“…Compared to chitin, chitosan is unique and found only in fungi that have deacetylase enzymes.
10.1080/21501203.2018.1473299-F0001Figure 1.Structural homology of linear polysaccharides. Chitin, chitosan and cellulose (Azuma et al 2015).
…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a natural, bio-degradable, non-toxic polymer derived from deaceylation of chitin. Chitosan has several reports for its clinical applications such as burns, wounds, nanoparticle based treatments and tissue regeneration [22]. ZnO quantum dots also finds significance for its applications in many areas for its attractive florescence properties [23].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan receives increasing attention as one of the promising renewable polymeric materials for various applications, such as wound healing and hemostatic activity [3,4,8,9]. Cheung et al reported [10] bio-molecules of marine origin with a defense action against pathogenic viruses and fungi.…”
mentioning
confidence: 99%
“…Chitin is reported as the second most common polymer after cellulose in nature, existing in the shells of crustaceans, like shrimp [4][5][6][7]. Chitosan receives increasing attention as one of the promising renewable polymeric materials for various applications, such as wound healing and hemostatic activity [3,4,8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation